Official Foreign Exchange Intervention - Canales Kriljenko, Jorge; Guimaraes, Roberto; Ishii, Shogo; Karacadag, Cem. (Washington, D.C. : International Monetary Fund, 2006)
Despite increasing exchange rate flexibility, central banks in emerging markets still intervene in their foreign exchange markets for several reasons. In doing so, they face many operational questions, including on the degree of transparency and the choice of markets and counterparties. This paper identifies elements of best practice in official foreign exchange intervention, presents survey evidence on intervention practices in developing countries, and assesses the effectiveness of intervention in Mexico and Turkey.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet